Routine immunization services in the light of COVID-19 pandemic - Varughese, Chinnu Sara; Shah, Anuradha Kunal (International Journal Of Community Medicine And Public Health, 2020)
World immunisation week is observed every year in the last week of 24th April to 30th April. Many parts of the world are still reeling under the threats of vaccine-preventable diseases (VPDs) and the importance of vaccination cannot be understated even in times of any other crisis. Worldwide, millions of children are saved from the grip of infectious diseases like polio and measles, and annually, around 2 to 3 million deaths are being averted. Routine immunization services, mass vaccination campaigns, catch up, and mop up sessions through outreach activities form part of the vaccine delivery strategies.